Incidencia del compromiso ético y moral de los profesionales de la comunicación en el ejercicio del periodismo en el cantón Quevedo año 20221 - Monte Pereira, Lisbeth Alexandra (2022)
The present work deals with an analysis towards a reality that conditions the future of social communicators with the incidence of ethical and moral commitment in the exercise of journalism that it has become a phenomenon that harms their professional life. the shared responsibilities at the global level where our communicators are experiencing changes that are detrimental to the future. This research seeks to know the incidence of the ethical and moral commitment of communication professionals in the exercise of journalism in the Quevedo canton in 2021, and alternative solutions to the stated problem can be found that help to positively change it. The main axis of ethics and morals aims to define itself as a set of norms and moral values that professionals in a certain sector must respect during the exercise of their profession. It translates into a series of behaviors and action guidelines aimed at promoting good labor practices and social harmony The survey technique was carried out using the questionnaire instrument that was applied through the tool (Google from) to the journalists of the Quevedo canton, which concluded that Ethics and Morals is the main source of journalism, since of seeks equality, the hidden truth, freedom since society has the right to know the information and demands that professionals investigate beyond a simple interest and thus provide information in the most truthful and free way.